Macrophage immunophenotype but not anti-inflammatory profile is modulated by peroxisome proliferator-activated receptor gamma (PPAR gamma) in exercised obese mice - Silveira, Loreana Sanches [UNESP]; Biondo, Luana Amorim; Souza Teixeira, Alexandre Abilio de; Lima Junior, Edson Alves de; Castoldi, Angela; Saraiva Camara, Niels Olsen; Festuccia, Willian T.; Rosa-Neto, Jose Cesar; Lira, Fabio Santos [UNESP] (W W F Verlagsgesellschaft Gmbh, 2020)
Moderate aerobic training may be therapeutic for chronic low-grade inflammatory diseases due to the associated antiinflammatory response that is mediated by immune cells. The peroxisome proliferator-activated receptor gamma (PPAR gamma) regulates the M1 (pro-inflammatory) and M2 (anti-inflammatory) polarization, as well as the immunometabolic response of macrophages. Against this background, the present study seeks to clarify whether the conditional deletion of PPAR gamma in macrophages would have any effect on the anti-inflammatory role of moderate aerobic training. To test this hypothesis, two mice strains were used: PPAR gamma LyzCre+/+ (KO) and littermates control animals (WT). Each genotype was divided into 1) sedentary high-fat diet (HF) and 2) high-fat diet and moderate aerobic training (HFT) (n = 5-8 per group). The experimental protocol lasted for 12 weeks, comprising 4 weeks of HF diet only and 8 weeks of HF diet and aerobic training (5 times/week, 50-60 minutes/day at 60% of maximum speed). Metabolic analyses were carried out on the serum glucose homeostase, adipose tissue morphology and cytokine content, and macrophage cytokine production. Immunophenotyping and gene expression were also performed. KO male mice were more prone to hypertrophy in the subcutaneous adipose tissue, though only the IL-1 beta (p = 0.0049) was higher compared to the values observed in WT animals. Peritoneal macrophages from KO animals exhibited a marked inflammatory environment with an increase in TNF-alpha (p = 0.0008), IL-1 beta (p = 0.0017), and IL-6 (p < 0.0001) after lipopolysaccharide stimulation. The moderate aerobic training protected both genotypes from weight gain and reduced the caloric intake in the KO animals. Despite the attenuation of the M2 marker CD206 (p < 0.001) in the absence of PPAR-gamma, the aerobic training modulated cytokine production in LPS stimulated peritoneal macrophages from both genotypes, reducing proinflammatory cytokines such as TNF-alpha (p = 0.0002) and IL-6 (p < 0.0001). Overall, our findings demonstrate the essential role of PPAR gamma in macrophage immunophenotypes. However, the deletion of PPAR gamma did not inhibit the exercise-mediated anti-inflammatory effect, underscoring the important role of exercise in modulating inflammation.
Keywords: adipose tissue; cytokines; immune system; moderate aerobic training; transcriptional factor